Molecular epidemiological characteristics of SARS-CoV-2 in imported cases from 2021 to 2022 in Zhejiang Province, China - Zhou, Biaofeng; Sun, Yi; Mao, Haiyan; Su, Lingxuan; Lou, Yihan; Yan, Hao; Yao, Wenwu; Chen, Honghu; Zhang, Yanjun (Frontiers in Public Health, 2023)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a global threat since 2020. The emergence of the Omicron variant in 2021, which replaced Delta as the dominant variant of concern, has had significant adverse impact on the global economy and public health. During this period, Zhejiang Province implemented dynamic zeroing and focused on preventing imported cases. To gain clear insight into the regional characteristics of imported COVID-19 cases, we conducted a systematic molecular epidemiological analysis of 146 imported cases between July 2021 and November 2022 in Zhejiang Province. Our study identified critical months and populations for surveillance, profiled the variation of various lineages, determined the evolutionary relationships among various lineages of SARS-CoV-2, and compared the results in Zhejiang with those obtained worldwide during this period. The study findings thus provide valuable insight and guidance on risk assessment, prevention, and control of future COVID-19 outbreaks.